2015
DOI: 10.31018/jans.v7i2.732
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethylene on physiological and biochemical parameters in different crop plants - A review

Abstract: A phytohormone may be defined as an organic substance other than a nutrient active in very minute amounts which is formed in certain parts of all plants and which is usually translocated to other sites, where it evokes specific biochemical, physiological and morphological responses. The gaseous plant hormone ethylene modulates many internal processes and growth responses to environmental stimuli. Ethylene is known to exert its effects by altering gene expression both at transcriptional and post-transcriptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…'BR1' , the positive effect on gas exchange parameters coincided with restoration of the action of antioxidant enzymes, which resulted in an increase in SOD (45%), CAT (129%), and APX (60%) indices. In the literature, it is reported that physiological and biochemical processes in plants are closely related, with effects intrinsically associated in cascades (Pahwa & Ghai, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…'BR1' , the positive effect on gas exchange parameters coincided with restoration of the action of antioxidant enzymes, which resulted in an increase in SOD (45%), CAT (129%), and APX (60%) indices. In the literature, it is reported that physiological and biochemical processes in plants are closely related, with effects intrinsically associated in cascades (Pahwa & Ghai, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Heat accumulation was computed as growing degree hours (GDH), according to the method proposed by Anderson et al [ 9 ]. In this model, hourly temperatures less than 4.5 °C registered no GDH; temperatures in the interval of 4.5–25 °C were adjusted by subtracting 4.5 °C; and temperatures greater than 25 °C were registered as 20.5 (25–4.5) °C.…”
Section: Methodsmentioning
confidence: 99%
“…Ethephon (2-chloroethylphosphonic acid) is an ethylene-based PGR that has demonstrated effectiveness in protecting fruit trees against spring frosts. Ethephon decomposes to ethylene after entering plant cells, and its effects are generally attributed to ethylene [ 9 ]. Many studies have documented that fall applications of ethephon can delay bloom in many fruit species, especially stone fruits.…”
Section: Introductionmentioning
confidence: 99%
“…Low temperature regulates seed germination by mediating ABA and GA metabolism and signaling, and the two hormones antagonistically promote seed coat and endosperm rupture ( MacGregor et al., 2015 ). As a plant growth regulator (PGR) that releases ethylene, ethephon can delay the flowering of many plants, greatly reducing the chance of freezing damage ( Pahwa and Ghai, 2015 ). Ethephon can delay flowering and prolong the dormant period of flower buds by increasing cooling and improving the cold tolerance of flower buds ( Durner and Gianfagna, 1991 ).…”
Section: Molecular Regulatory Mechanism Of Plants’ Response To Low-te...mentioning
confidence: 99%